2017
DOI: 10.1007/s00704-017-2290-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of satellite daily rainfall estimates in complex terrain of Bali Island, Indonesia

Abstract: Satellite rainfall products have different performances in different geographic regions under different physical and climatological conditions. In this study, the objective was to select the most reliable and accurate satellite rainfall products for specific, environmental conditions of Bali Island. The performances of four spatio-temporal satellite rainfall products, i.e., CMORPH 25 , CMORPH 8 , TRMM, and PERSIANN, were evaluated at the island, zonation (applying elevation and climatology as constraints), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 56 publications
(71 reference statements)
3
28
1
Order By: Relevance
“…The comparison of gauge-based assessment studies confirmed the spatial variability of SPE efficiency in reproducing precipitation, so no single SPE can be said to be the most effective one at global scale. For example, when TMPA, CMORPH, and PERSIANN SPE datasets were compared, TMPA was found to be closer to the observed precipitation in India (Prakash et al, 2014), the Guyana shield (Ringard et al, 2015), Africa (Serrat-Capdevila et al, 2016), Chile (Zambrano-Bigiarini et al, 2017) and South America Andean plateau (Satgé et al, 2016), whereas CMORPH was closer to observed precipitation in Bali, Indonesia (Rahmawati and Lubczynski, 2017), Pakistan (Hussain et al, 2017), and China (Su et al, 2017;Zeng et al, 2018). However, these assessments based on comparison with gauge observations did not assess SPE's potential performance over unmonitored regions.…”
Section: State Of the Art Evaluation Of Spesmentioning
confidence: 87%
“…The comparison of gauge-based assessment studies confirmed the spatial variability of SPE efficiency in reproducing precipitation, so no single SPE can be said to be the most effective one at global scale. For example, when TMPA, CMORPH, and PERSIANN SPE datasets were compared, TMPA was found to be closer to the observed precipitation in India (Prakash et al, 2014), the Guyana shield (Ringard et al, 2015), Africa (Serrat-Capdevila et al, 2016), Chile (Zambrano-Bigiarini et al, 2017) and South America Andean plateau (Satgé et al, 2016), whereas CMORPH was closer to observed precipitation in Bali, Indonesia (Rahmawati and Lubczynski, 2017), Pakistan (Hussain et al, 2017), and China (Su et al, 2017;Zeng et al, 2018). However, these assessments based on comparison with gauge observations did not assess SPE's potential performance over unmonitored regions.…”
Section: State Of the Art Evaluation Of Spesmentioning
confidence: 87%
“…This may be due to poorly resolved land-sea constrasts or orography, even at 25-km grid spacing, as orographic effects have been observed to impact TC precipitation (Tan et al 2012;Racoma et al 2016). However, TRMM also has errors over complex orography (Rahmawati and Lubczynski 2018) so there may also be observation errors over the Philippine islands. Improvements in the system over time are encouraging, but biases remain considerable.…”
Section: Discussionmentioning
confidence: 99%
“…With advancement in RS techniques, various satellite rainfall products at different spatial and temporal resolutions are now readily available and their spatial and temporal resolution increases. However, these rainfall products still need to be validated against in situ data to select the optimal product and eventually to remove the bias (Lekula et al 2018b;Rahmawati and Lubczynski 2017). Also satellite-derived PET data are available as an RS product, although not as widely as rainfall and at much coarser spatial and temporal resolution.…”
Section: Experience Of Using Remote Sensing In Data-scarce Central Kamentioning
confidence: 99%